Seguimiento fisicoquímico de la calidad de agua de una laguna facultativa de un ingenio azucarero respecto al suministro de nutrientes al sistema microbiano - López Parra, Lizbeth Lorena (Universidad Santiago de Cali, 2020)
Generally, in the treatment of domestic, agricultural and industrial wastewater lagoon systems of anaerobic, aerobic and facultative type are used with the purpose of eliminating the polluting agent that can reach a natural body of water can consume the existing oxygen and collapse all the life forms. This chapter focuses on the diagnosis of an oxidation facultative lagoon present in a Sugar Mill, analyzing in three critical points, the coloration, the sulfur, the nitrogen, the phosphorus, the calcium, the magnesium and the relation between the nutrients with the chemical demand of oxygen, the biochemical demand of oxygen and the dissolved total solids. From this we found an inappropriate relationship between the symbiotic processes between algae and bacteria, which contributes to a loss of efficiency in the process of removal of organic matter.